Artery Tertiary Lymphoid Organs: Powerhouses of Atherosclerosis Immunity - Yin, Changjun; Mohanta, Sarajo Kumar; Srikakulapu, Prasad; Weber, Christian; Habenicht, Andreas J. R. (Frontiers in Immunology, 2016)
Artery tertiary lymphoid organs (ATLOs) are atherosclerosis-associated lymphoid aggregates with varying degrees of complexity ranging from small T/B-cell clusters to well structured lymph node-like though unencapsulated lymphoid tissues. ATLOs arise in the connective tissue that surrounds diseased arteries, i.e. the adventitia. ATLOs have been identified in aged atherosclerosis-prone hyperlipidemic apolipoprotein-deficient (ApoE-/-) mice: They are organized into distinct immune cell compartments including separate T-cell areas, activated B-cell follicles, and plasma cell (PC) niches. Analyses of ATLO immune cell subsets indicate antigen-specific T- and B-cell immune reactions within the atherosclerotic arterial wall adventitia. Moreover, ATLOs harbor innate immune cells including a large component of inflammatory macrophages, B-1 cells, and an aberrant set of antigen-presenting cells (APCs). There is marked neoangiogenesis, irregular lymphangiogenesis, neoformation of high endothelial venules (HEVs), and de novo synthesis of lymph node-like conduits. Molecular mechanisms of ATLO formation remain to be identified though media vascular smooth muscle cells (VSMCs) may adopt features of lymphoid tissue organizer- (LTo) like cells by expressing lymphorganogenic chemokines, i.e. CXCL13 and CCL21. Although these data are consistent with the view that ATLOs participate in primary T- and B-cell responses against elusive atherosclerosis-specific autoantigens, their specific protective or disease-promoting roles remain to be identified. In this review, we discuss what is currently known about ATLOs, their potential impact on atherosclerosis, and make attempts to define challenges ahead.